The level of Malay language proficiency of non-native students and its relationship with a second language learning motivation - Nahar, Nora Azian; Abd Rahman, Fadzilah (Universiti Putra Malaysia Press, 2018)
The proficiency of the Malay language should be the main platform of developing a nation in Malaysia. Previous studies found that non-Malay students in Malaysia were less proficient in listening, speaking, reading, and less skilful in writing in Malay. Thus, this study was conducted to identify the level of proficiency of Malay language of non-Malay speakers and their relationships with learning motivation. A total of 414 samples from five national primary schools, Chinese vernacular primary schools and Indian vernacular primary schools were selected. The analysis was done using the UPBM_SR Test set and questionnaire. Data is processed using IBM SPSS version 23 with the cross-sectional design. The findings show that the majority of the respondents achieved Level 4 for all the skills (listening, speaking, reading and writing) and the relationship between UPBM_SR Overall Min Score with learning motivation (instrumental and integrative) was found to have significant minor relevance. It is apparent that non-Malay students need to improve their self motivation in learning the second language and all parties need to cooperate to ensure that every student in Malaysia is proficient in using the national language.